La cultura escrita en los monasterios femeninos del Císter en Portugal (siglos XIII-XV) - Rêpas, Luís Miguel (2022)
PTDC/ART-HIS/29522/2017 PTDC/ART-HIS/0739/2020 DL 57/2016/CP1453/CT0070 UIDB/00749/2020 UIDP/00749/2020